2010
DOI: 10.1186/1758-5996-2-59
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in menopausal transition: Isfahan Healthy Heart Program, a population based study

Abstract: IntroductionThere is a remarkable increase in cardiovascular disease after menopause. On the other hand, metabolic syndrome as a collection of risk factors has a known effect on cardiovascular diseases. Hormone changes are considered as one of the main relevant factor regarding cardiovascular disease as well as some recognized relationship with metabolic syndrome's components. This study was carried out in order to search for prevalence of metabolic syndrome during menopausal transition.MethodIn a cross sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
5
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 27 publications
9
45
5
4
Order By: Relevance
“…Heidari et al described the prevalence of MetS was 44.9%, 57.9% and 64.3% in premenopausal, perimenopausal and postmenopausal women respectively which was comparable to this results. 7 In a study by Figueiredo et al, the prevalence of MetS using IDF criteria was 64.5% which was comparable to this study. 8 However, the same criteria used by Pandey and colleagues documented the prevalence of 55% in Western India.…”
Section: Discussionsupporting
confidence: 75%
“…Heidari et al described the prevalence of MetS was 44.9%, 57.9% and 64.3% in premenopausal, perimenopausal and postmenopausal women respectively which was comparable to this results. 7 In a study by Figueiredo et al, the prevalence of MetS using IDF criteria was 64.5% which was comparable to this study. 8 However, the same criteria used by Pandey and colleagues documented the prevalence of 55% in Western India.…”
Section: Discussionsupporting
confidence: 75%
“…The prevalence of MS among postmenopausal women has been reported to (15), and 64.3% in Iran (16). MS is one factor that increases the mortality rate in both men and women (17).…”
Section: Discussionmentioning
confidence: 99%
“…3 Some other study reported that greater increased in waist-to-hip ratio and waist circumference, body mass index in postmenopausal women than that of premenopausal women. [10][11][12] Opposite nding was reported by some investigators who did not nd any signi cant di erence in BMI value in premenopausal and postmenopausal women. Some studies have been done on this regard in abroad but no published data has yet been available on this aspect in our country.…”
Section: Introductionmentioning
confidence: 76%